Development of a corpus of Malaysian KBSM engineering texts and related word list - Ng, Yu Jin (2015)
Engineering students are required to read Engineering textbooks which are specialized in nature, containing significant amount of Engineering vocabulary and terminology. There is a language need for better comprehension of Engineering concepts and this can be done by focusing on the frequent and essential Engineering vocabulary required. In addition, since most English Language Teaching (ELT) teachers are non-specialists in the field of Engineering, they can be unguided when it comes to the teaching of required Engineering vocabulary in a classroom. Furthermore, the core problem concerning the Malaysian textbooks is that the textbooks produced are not based on any essential word lists or corpora in the syllabus. Thus, evaluating and analyzing the specialised textbooks is a substantial way to highlight the importance of lexical components for the Engineering students to initiate them into their discourse community and for ELT teachers who teach English for Specific Purposes (ESP) courses in Engineering. Since there is no existing corpus available on the language applied in the teaching and learning of Engineering subjects in English, this study aims to develop an Engineering vocabulary corpus from the prescribed Malaysian KBSM Vocational Engineering Textbooks (MKVET). The corpus was then used to create the Engineering Word List (EnWL) with the properties of technical and semi-technical engineering vocabulary. The aims of the study were (1) To develop a pedagogic Engineering corpus from the Malaysian KBSM Vocational Engineering Textbooks (MKVET); (2) To investigate the similarities and differences in the vocabulary loading or distribution patterns of the Engineering textbooks when compared to the Malaysian KBSM Sciences and English in vocational schools. (3) To develop a specialised Engineering Word List (EnWL) from the created corpus and to determine the lexical patterns of language use in the Engineering textbooks in terms of noun compounds. These objectives were addressed in four research questions and the research design used was content analysis (corpus linguistics approach) to obtain data. The reliable concordance software was the WordSmith Tools Version 5.0 (Scott, 2008) and RANGE (Heatley, Nation & Coxhead, 2002) were used for the purpose of text analysis and word list development. The corpus is made up of 391,505 words (15,621 types) and the EnWL consists of 842 word families (1,704 types). Thus, the developed corpus and word list can be easily used by other researchers. The word selection criteria used in generating the EnWL is novel for detailed investigation in determining the essential Engineering words. This study suggests the usage of the General Service List (GSL), Academic Word List (AWL) and EnWL for Engineering students to gain greater benefit from word list learning in terms of text coverage. In addition, the suggested noun compounds for English for Engineering Purposes (EEP) provide extended insights to teachers and students to deal with the arbitraries in Engineering language, especially when noun compounds do not follow a specific pattern or hierarchy. With the EnWL and the Engineering corpus, the findings provide a foundation for teachers, textbook writers, syllabus designers and curriculum planners to design and develop more relevant and lexically guided materials to arrive at effective pedagogic approaches in teaching vocabulary.